2017
DOI: 10.3390/antib6020006
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Autoantibodies and Their Relationship to CCP Antibodies and Rheumatoid Factor in the Progression of Early Rheumatoid Arthritis

Abstract: Serum autoantibodies to cyclic citrullinated peptides (anti-CCP) and rheumatoid factor (RF) are important markers for diagnosis and prognosis of rheumatoid arthritis (RA), but their autoantigens are not cartilage-specific. Autoantibodies to joint-specific type II collagen (CII) also occur in RA, and monoclonal antibodies of similar specificity induce collagen antibody-induced arthritis in animals, but their role in RA is uncertain. We utilized an enzyme-linked immunosorbent assay (ELISA) with the CB10 peptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…As generally accepted, RF and anti-CCP antibodies are important markers for the diagnosis and prognosis of RA ( 53 ). Numerous clinical data have shown that RF is not specific for RA diagnosis, and approximately 30% to 45% of patients with RA do not have RF ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…As generally accepted, RF and anti-CCP antibodies are important markers for the diagnosis and prognosis of RA ( 53 ). Numerous clinical data have shown that RF is not specific for RA diagnosis, and approximately 30% to 45% of patients with RA do not have RF ( 54 ).…”
Section: Resultsmentioning
confidence: 99%
“…CII activates innate and adaptive immune responses, which have a primary role in the initiation and pathogenesis of RA in CIA model. Some studies found that anti-CII antibodies are present in the serum and synovial fluid of RA patients precede the onset of joint symptoms ( Mullazehi et al, 2007 ; Whittingham et al, 2017 ). Patients with positive anti-CII antibodies exhibited higher disease activity and more severe symptoms ( Mullazehi, et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Auto-reactive B cell produces anti-cyclic citrullinated peptides antibody (ACPA), rheumatoid factor (RF) and anti-type II collagen (CII). [3][4][5] ACPA is found to be about 95% of RA cases and has the highest specificity among the three autoantibodies. 6,7 ACPA is primarily noticed as the persistent protein in the joint or circulation that contributes to the formation of the immune complex causes inflammation and joint destruction.…”
Section: Introductionmentioning
confidence: 96%